Community College International Student Research: A Critical Time Series Analysis (Comparative & International Education Series, 2021)
Chapter 2|22 pages Community College International Student Research: A Critical Time Series AnalysisBy Rosalind Latiner RabyThis chapter uses a time series analysis to capture patterns in publications over time in the study of US community college international students. It reviews 305 forms of scholarship published from 1950 to 2020. Critical analysis is used to see how publications influence what and whose scholarship matters, what narratives are found in the publications and whose voices are missing, and if the publications support or counter dominant knowledge dissemination. Time series analysis is used to chart patterns in publications over time. Findings show that publications on community college international students have existed for multiple decades and yet are marginalized in the field. In moving forward, it is important for practitioners and researchers to understand the existing wealth of publications on community college international students.